2011
DOI: 10.1590/s1516-35982011001100005
|View full text |Cite
|
Sign up to set email alerts
|

Influência da irrigação, da densidade de plantio e da adubação nitrogenada nas características morfogênicas, estruturais e de produção do capim-tanzânia

Abstract: O experimento foi conduzido com os objetivos de avaliar a altura do dossel com 95% de interceptação luminosa e quantificar a influência da adubação nitrogenada e da densidade de plantas nas características morfogênicas e estruturais de capim-tanzânia. Quatro doses de nitrogênio, N (0, 80, 160 e 320 kg.ha-1), foram combinadas com três densidades de plantas (9, 25 e 49 plantas.m-2), em um arranjo fatorial 4 × 3, em delineamento inteiramente casualizado com três repetições, para avaliação da produção de biomassa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
1
8
1
4
Order By: Relevance
“…The Pasture, due to its low production cost compared to the concentrates, represents the most practical and economical way to feed the cattle, it forms the livestock farming basis in Brazil (MAGALHÃES et al, 2011).However, the economic results obtained by most farmers, with the production in pasture, can be considered very modest in relation to the great potential of the country. The animal production system in pasture is the largest conditioning factor of competitiveness, but with a great challenge to be overcome: the maintenance of pasture supply in quantity and quality (ALENCAR et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The Pasture, due to its low production cost compared to the concentrates, represents the most practical and economical way to feed the cattle, it forms the livestock farming basis in Brazil (MAGALHÃES et al, 2011).However, the economic results obtained by most farmers, with the production in pasture, can be considered very modest in relation to the great potential of the country. The animal production system in pasture is the largest conditioning factor of competitiveness, but with a great challenge to be overcome: the maintenance of pasture supply in quantity and quality (ALENCAR et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, the higher frequency of cuts in higher doses may have influenced the pseudostems rate of elongation, because plants from plots that received higher dose of nitrogen sprouted and developed their morphological components faster, staying longer in a position of shading themselves, thereby increasing the total dry mass of pseudostems. Greater accumulation of TDMPS with nitrogen was also observed by Martuscello et al (2004) in Massai grass and by Magalhães et al (2011), in Tanzania grass. The reduction in the production of TDMPS with the increase of density was contrary to the results described in the literature, since higher densities result in increased stem elongation of plants, because of bigger competition for light.…”
Section: Resultsmentioning
confidence: 66%
“…Magalhães et al (2011) also observed the effect of plant densities in the establishment of Tanzania grass. In this experiment with Mombasa grass, the largest number of plants per unit area resulted in the shortest period of plant growth to reach 95% of the lowest densities in relation to light interception.…”
Section: Resultsmentioning
confidence: 86%
“…Ausência de diferença na TApF e no FIL também foi observada por Magalhães et al (2011) O efeito da adubação nitrogenada sobre a TApF é apresentado de forma variável na literatura e, de acordo com Gastal e Nelson (1994), é pequeno o efeito do nitrogênio sobre esta variável em gramíneas com hábito de crescimento cespitoso. Roma et al (2012) observaram efeito da adubação nitrogenada sobre a TApF em capim-Tanzânia adubado com nitrogênio (zero, 100, 200 e 300 kgN ha.ano -1 ) e, em pastejo com lotação intermitente (crescimento livre das plantas).…”
Section: Resultsunclassified